CO2 Chemisorption Behavior of Coordination‐Derived Phenolate Sorbents. Issue 14 (1st June 2021) - Suo, Xian; Yang, Zhenzhen; Fu, Yuqing; Do‐Thanh, Chi‐Linh; Chen, Hao; Luo, Huimin; Jiang, De‐en; Mahurin, Shannon M.; Xing, Huabin; Dai, Sheng
Abstract: CO2 chemisorption via C−O bond formation is an efficient methodology in carbon capture especially using phenolate‐based ionic liquids (ILs) as the sorbents to afford carbonate products. However, most of the current IL systems involve alkylphosphonium cations, leading to side reactions via the ylide intermediate pathway. It is important to figure out the CO2 chemisorption behavior of phenolate‐derived sorbents using inactive and easily accessible cation counterparts without active protons. Herein, phenolate‐based systems were constructed via coordination between alkali metal cations with crown ethers to avoid the participation of active protons in CO2 chemisorption. Reaction pathway study revealed that CO2 uptake could be achieved by O−C bond formation to afford carbonate. CO2 uptake capacity and reaction enthalpy were significantly influenced by the coordination effect, alkali metal types, and alkyl groups on the benzene ring. Abstract : Sorbent study : CO2 chemisorption behavior of a phenolate‐based system is studied taking advantage of the coordination between alkali metal cations with crown ethers, and regulation over CO2 uptake capacity and reaction enthalpy is achieved by tuning the coordination effect, alkali metal types, and alkyl substituents.